Tower of Power: The Drummond Medical Building and the Interwar Centralization of Medical Practice - Theodore, David; Burke, Stacie; Adams, Annmarie (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2009)
AbstractThis paper focuses on Montreal’s Drummond Medical Building (1929), designed by the well-known architectural firm of Nobbs & Hyde, as a case study of the new typology that emerged in urban Canada in the 1920s: a modern, purpose-built high-rise for healthcare professionals, with elevators, telephones, indoor parking, and retail shops, located in an upscale commercial district. What role did medical high-rises play in the practice of modern medicine? We speculate that these clinics marked the end of the house-office era across Canada, centralizing the practice of healthcare professionals. This CIHR-funded project illustrates complex social and physical networks among architects and doctors, drawing attention to the importance of studying architecture as a technology in the history of modern medicine.